Investigation of optical fiber based chemical sensors - Lim, Januarius Chih Kian (2014)
Optic fiber exhibiting great advantages including high capacity, low signal degradation and immune to electromagnetic interference, has been extensively applied in the fields of optical communication and optical sensing. Especially, optical fiber based sensors to monitor the environmental changes have shown potential usefulness in our daily life covering medicine and chemical industries, food manufactory, bridge monitoring and so on. For the past 40 over years, it has been constantly under development and has produced many products and new technologies related to optical fiber sensors. In the project, we will concentrate on a scheme of optic fiber chemical sensor based on multimode interference and carbon nanotubes (CNTs) to enhance sensitivity. This report mainly involves three aspects: fiber based chemical sensors, refractive index sensing and temperature sensing.